A specific DNA methylation profile correlates with a high risk of disease progression in stage I classical (Alibert‐Bazin type) mycosis fungoides. (1st June 2014) - Ferrara, G.; Pancione, M.; Votino, C.; Quaglino, P.; Tomasini, C.; Santucci, M.; Pimpinelli, N.; Cusano, F.; Sabatino, L.; Colantuoni, V.
Summary: Background: Mycosis fungoides (MF) is the most common type of cutaneous T‐cell lymphoma; in its classical presentation it evolves slowly, but it can have an aggressive course in a subset of patients. Objectives: To investigate the impact of epigenetic mechanisms on the progression of early stage MF. Methods: We analysed DNA methylation at 12 different loci and long interspersed nucleotide elements‐1 (LINE‐1), as a surrogate marker of global methylation, on tissue samples from 41 patients with stage I MF followed up for at least 12 years or until disease progression. The methylation profiles were also analysed in two T‐cell lymphoma cell lines and correlated with gene expression. Results: The selected loci were methylated in a tumour‐specific manner; concomitant hypermethylation of at least four loci was more frequent in cases progressing within 1–3 and 3–6 years than in late‐progressive or non‐progressive cases. LINE‐1 methylation was significantly lower in rapidly progressive MF at 3 years (61%, P < 0·001) than in those at 12 years (67%). PPARG, SOCS1 and NEUROG1 methylation showed remarkable differences among the prognostic groups, but only PPARG was a significant predictor of disease progression within 6 years, after adjustment for patients' age or gender. Strikingly, a methylation profile similar to progressive cases was found in highly proliferative Sézary‐derived HUT78 cells but not in MF‐derived HUT102 cells. Exposure to a DNA demethylating agent restored sensitivity to apoptosis and cell cycle arrest. Conclusions: Epigenetic silencing of specific biomarkers can predict the risk of disease progression in early‐stage MF, providing insights into its pathogenesis, prognosis and therapy.